WATER-SOLUBLE FILM SEBAGAI ALTERNATIF KEMASAN PRODUK SACHET - Andra Rizky Yuwono (Universitas Trisakti, 2019)
AbstractTrash has always been a problem for the world. Trash are items that no longer have any use and havebeen thrown away by their owner(s). Current estimations show that Indonesia produces 85.000 tonsof daily trash, with further estimations showing an increase up to 150.000 tons of trash per day, a76% increase, by the year 2025. Water-soluble films are films that can dissolve or degrade when theycome into contact with water, made from polyvinyl alcohol (PVA) polymers. From the year 2012, thismaterial has been used in America detergent packaging, spa cosmetics, and many others. Water-solublefilms are environmental-friendly products that brings several advantages, such as total solubility inwater, biodegradability, pollution- and poison-free, and anti-stasis. Product packaging made of theenvironmentally-friendly water-soluble films is now necessary due to the high amount of global trashproduction and the resulting concerns about non-degradable wastes. With water-soluble film-basedpackaging as an alternative to sachet-based packaging, it is expected that there will be a reduction todaily trash production, which leads to well-kept environments.Keywords: packaging, plastic, environmentally-friendly, trash, water-soluble film